“It was an awful mistake with that girl. Advise me what to do.” On Jaroslav Hašek’s bigamy - Czaplińska, Joanna (The Opole Studies in Administration and Law, 2020)
In this article, Jaroslav Hašek’s bigamy will be discussed from two points of view – the biographical and legal ones. In almost every writer’s biography, the fact of his marrying two women is mentioned, but it is also quickly dismissed with only a few words of explanation. In the author’s opinion, after almost a hundred years following Hašek’s death, the case of his bigamy deserves proper interpretation.